Exploring the implementation of an electronic record into a maternity unit: a qualitative study using Normalisation Process Theory. Issue 1 (December 2017) - Scantlebury, Arabella; Sheard, Laura; Watt, Ian; Cairns, Paul; Wright, John; Adamson, Joy
Abstract Background To explore the benefits, barriers and disadvantages of implementing an electronic record system (ERS). The extent that the system has become 'normalised' into routine practice was also explored. Methods Qualitative semi-structured interviews were conducted with 19 members of NHS staff who represented a variety of staff groups (doctors, midwives of different grades, health care assistants) and wards within a maternity unit at a NHS teaching hospital. Interviews were conducted during the first year of the phased implementation of ERS and were analysed thematically. The four mechanisms of Normalisation Process Theory (NPT) (coherence, cognitive participation, collective action and reflexive monitoring) were adapted for use within the study and provided a theoretical framework to interpret the study's findings. Results Coherence (participants' understanding of why the ERS has been implemented) was mixed – whilst those involved in ERS implementation anticipated advantages such as improved access to information; the majority were unclear why the ERS was introduced. Participants' willingness to engage with and invest time into the ERS (cognitive participation) depended on the amount of training and support they received and their willingness to change from paper to electronic records. Collective action (the extent the ERS was used) may be influenced by whether participants perceived there to be benefits associated with the system. Whilst some individuals reported benefits such as improved legibility of records, others felt benefits were yet to emerge. The parallel use of paper and the lack of integration of electronic systems within and between the trust and other healthcare organisations hindered ERS use. When appraising the ERS (reflexive monitoring) participants perceived the system to negatively impact the patient-clinician relationship, time and patient safety. Conclusions Despite expectations that the ERS would have a number of advantages, its implementation was perceived to have a range of disadvantages and only a limited number of 'clinical benefits'. The study highlights the complexity of implementing electronic systems and the associated longevity before they can become 'embedded' into routine practice. Through the identification of barriers to the employment of electronic systems this process could be streamlined with the avoidance of any potential detriment to clinical services.